Safety, pharmacokinetics, and pharmacodynamics of PD 0348292, an oral, direct factor Xa inhibitor, after single and multiple dosings in healthy subjects. Issue 1 (5th November 2015) - Xuan, Dawei; McBride, Scott; Wastall, Philip; Porcari, Anthony; DiCarlo, Lorenzo; Boyd, Rebecca A.
Abstract: Objective: The objective of this study was to evaluate PD 0348292 safety, pharmacokinetics, and pharmacodynamics in healthy subjects. Methods: Three phase 1 studies were conducted. Studies 1001 and 1021 were single ascending‐dose studies in healthy subjects randomized to oral PD 0348292 (2.5–150 and 0.1–2.5 mg, respectively) or placebo. Study 1003 was a multiple ascending‐dose study in which 3 cohorts of young subjects received multiple doses of PD 0348292 (5–30 mg) every 12 hours or placebo, and 1 cohort of elderly subjects received a single dose (5 mg) of PD 0348292 or placebo. Drug plasma concentrations were measured. The effects of PD 0348292 on thrombin generation and typical coagulation measures such as prothrombin time, and international normalized ratio were evaluated. Results: Single doses of PD 0348292 were well tolerated. Minor bleeding‐related adverse events were observed following multiple doses of PD 0348292. PD 0348292 exposure increased less than proportionally at doses > 20 mg. Median peak concentrations occurred 3 to 4 hours following administration, and the mean terminal t1/2 value was approximately 10 hours. PD 0348292 demonstrated robust and concentration‐dependent inhibition of thrombin generation, and modest and dose‐related increases in typical coagulation measures. Conclusions: The safety, pharmacokinetics, and pharmacodynamics of PD 0348292 were acceptable for future clinical development.